Distance caregivers of people with Alzheimer's disease and related dementia: a phenomenological study - Edwards, Megan, author; Kuk, Linda, 1950-, advisor; Sample, Pat L., advisor; Littrell, John M., 1944-, committee member; Greene, David Paul, committee member (Colorado State University. Libraries, 2010)
The population of distance caregivers of people with dementia/Alzheimer's disease has not been extensively researched. This research study focused on exploring the lived experience of people caring for someone with dementia/Alzheimer's disease from a distance (defined as 2 or more hours away) to help shed light on this caregiving population. Ten participants (all adult children caring for a parent with dementia/Alzheimer's disease) were involved in this qualitative, phenomenological study. Each participant took part in two individual interviews, the first interview being conducted in person (in most cases) and the follow-up interview being conducted over the phone. After the interviews were transcribed, I analyzed the data using Moustakas's (1994) modified Van Kaam Method. Each interview (initial and follow-up) was analyzed separately. The findings from each participant's two interviews were combined, and then data from all 10 participants were pooled together. Results have been written in story form, and may help readers understand the overall experience of being a distance caregiver for someone with dementia/Alzheimer's disease (including the struggles these caregivers might encounter and the resources they have found). The results of my study, recommendations for future research, and implications for health care professionals are discussed.
Keywords: Alzheimer's disease -- Patients -- Care -- Management; Alzheimer's disease -- Patients -- Family relationships; Caregivers -- Family relationships; Long-distance relationships; Continuum of care